2004
DOI: 10.1021/jp047619y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Ionic Liquids:  The Effect of Electronic Polarizability

Abstract: An electronically polarizable model has been developed for the ionic liquid 1-ethyl-3-methylimidazolium nitrate (EMIM + /NO 3 -). Molecular dynamics simulation studies were then performed on both the polarizable and nonpolarizable versions of the model. Comparisons of shear viscosity and diffusion constants at 400 K show that the effects of polarizability are quite substantial and the polarizable model results are in better agreement with the experimental values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
501
3
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 408 publications
(539 citation statements)
references
References 27 publications
34
501
3
1
Order By: Relevance
“…It is worth noticing that an increasing number of studies on room-temperature ionic liquids have involved models similar in spirit to the PIM (they mainly differ due to the choice of Lennard-Jones form to represent the van der Waals interactions). [120][121][122][123][124] For the moment the force-matching procedure was not used in these works, but we have recently extended it to the case of the 1-ethyl-3-methylimidazolium tetrachloroaluminate ionic liquid. 23 …”
Section: Discussionmentioning
confidence: 99%
“…It is worth noticing that an increasing number of studies on room-temperature ionic liquids have involved models similar in spirit to the PIM (they mainly differ due to the choice of Lennard-Jones form to represent the van der Waals interactions). [120][121][122][123][124] For the moment the force-matching procedure was not used in these works, but we have recently extended it to the case of the 1-ethyl-3-methylimidazolium tetrachloroaluminate ionic liquid. 23 …”
Section: Discussionmentioning
confidence: 99%
“…A significant body of work has appeared recently on the modeling and simulation of the thermodynamic properties of ILs [14][15][16][17][18][19][20][21][22][23] and their mixtures. 24,25 Efforts have also been undertaken to calculate the viscosity of ILs using equilibrium molecular dynamics simulations, [26][27][28][29] nonequilibrium molecular dynamics methods such as periodic perturbation, 30 and reverse nonequilibrium molecular dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…These studies modeled bulk properties, such as melting points, 8 diffusion, [8][9][10][11][12] and viscosity. 8,9 Radial distribution functions 8,10,[12][13][14][15][16] and densities have also been calculated. 8,10,15,17 Dynamics simulations have revealed that 1-ethyl-3-methylimidazolium nitrate has diffusion properties similar to those of a supercooled liquid.…”
Section: Introductionmentioning
confidence: 99%